The complete mitochondrial genome of Pseudopimelodus schultzi Dahl 1955 (Siluriformes, Pseudopimelodidae) and its phylogenetic position within Pseudopimelodidae. Issue 8 (3rd August 2021) - Yang, Hanwei; Ma, Xiuhui
Abstract: The complete mitochondrial DNA genome of Pseudopimelodus schultzi was first was determined in this study. The entire length of mitochondrial genome consists of 13 protein-codinggenes (PCG), 2 ribosomal RNA genes (rRNA), and 22 transfer RNA (tRNA) genes and control region. The nucleotide composition was made up of 32.2% A, 25.9% T, 26.7% C, and 15.2% G, respectively, indicating an A + T (58.1%)-rich feature. With the exception of 8 tRNA genes and NADH6, mitochondrial genes are encoded on the heavy strand, which was similar to that in other vertebrates. The results showed that the species of Pseudopimelodidae were gathered in the same branch. The phylogenies indicate monophyly of the genus Batrochoglanis, Batrochoglanis and Microglanis, respectively.